NILAINISASI ILMU DALAM ERA GLOBALISASI (SEBUAH UPAYA INTEGRASI ILMU DAN PEMBELAJARAN) - Hafizon, Ahmad; M, Amril (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of this study is to determine the value of knowledge in the era of globalization (an effort to integrate knowledge and learning). This study uses qualitative research. The results showed that: 1) the impact of the development of science and technology due to globalization, namely positive and negative, 2) the importance of value and moral education for children, 3) Integration of Science in Learning